First-trimester plasma tocopherols are associated with risk of miscarriage in rural Bangladesh. Issue 2 (26th November 2014) - Shamim, Abu Ahmed; Schulze, Kerry; Merrill, Rebecca D; Kabir, Alamgir; Christian, Parul; Shaikh, Saijuddin; Wu, Lee; Ali, Hasmot; Labrique, Alain B; Mehra, Sucheta; Klemm, Rolf DW; Rashid, Mahbubur; et al.
ABSTRACT: Background: Tocopherols were discovered for their role in animal reproduction, but little is known about the contribution of deficiencies of vitamin E to human pregnancy loss. Objective: We sought to determine whether higher first-trimester concentrations of α-tocopherol and γ-tocopherol were associated with reduced odds of miscarriage (pregnancy losses <24 wk of gestation) in women in rural Bangladesh. Design: A case-cohort study in 1605 pregnant Bangladeshi women [median (IQR) gestational age: 10 wk (8–13 wk)] who participated in a placebo-controlled vitamin A– or β-carotene–supplementation trial was done to assess ORs of miscarriage in women with low α-tocopherol (<12.0 μmol/L) and γ-tocopherol (<0.81 μmol/L; upper tertile cutoff of the γ-tocopherol distribution in women who did not miscarry). Results: In all women, plasma α- and γ-tocopherol concentrations were low [median (IQR): 10.04 μmol/L (8.07–12.35 μmol/L) and 0.66 μmol/L (0.50–0.95 μmol/L), respectively]. In a logistic regression analysis that was adjusted for cholesterol and the other tocopherol, low α-tocopherol was associated with an OR of 1.83 (95% CI: 1.04, 3.20), whereas a low γ-tocopherol concentration was associated with an OR of 0.62 (95% CI: 0.41, 0.93) for miscarriage. Subgroup analyses revealed that opposing ORs were evident only in women with BMI (in kg/m 2 ) ≥18.5 and serum ferritin concentration ≤150 μg/L, although low BMI and elevated ferritin conferred stronger risk of miscarriage. Conclusions: In pregnant women in rural Bangladesh, low plasma α-tocopherol was associated with increased risk of miscarriage, and low γ-tocopherol was associated with decreased risk of miscarriage. Maternal vitamin E status in the first trimester may influence risk of early pregnancy loss. The JiVitA-1 study, from which data for this report were derived, was registered at clinicaltrials.gov as NCT00198822.